A Comparative Study of Nesting Sites and Burrowing Habits of two Iranian Burrowing Scorpions - Babak Vazirianzadeh; Amir Jalali; Mostafa Chrom; Alireza Mohammady; Hassan Vatandoost; Forozan Panahi (Tehran University of Medical Sciences, 2017)
Background: The different features of scorpions can be successfully described by their nesting and burrowing behaviors. There is little information about burrowing activity of Iranian scorpions. Methods: The current study was performed to compare the burrowing behavior between two burrowing Iranian scorpions, Scorpio maurus and Odonthubutus bidentatus by describing 30 nests of each species regarding collecting the scorpions. Results: Scorpio maurus and O. bidentatus have a tendency to make nest with elliptical, round-like entrance and oval shape with arch at the top, respectively. There was not any significant difference between nest entrance properties of two scorpions. One-way ANOVA test showed that the height and diameter of two species nests were not significantly different. A Pearson correlation also showed a relative strong direct relationship between height and diameter of S. maurus nests than O. bidentatus. This correlation was not significant in the case of O. bidentatus. The results provided additional habitat information of scorpions. Conclusion: The nests morphology characteristics of two Iranian scorpions including shape, depth, length and diameter depend are different from each other based on the following factors: species, soil texture, soil moisture and region conditions.